Germanium-incorporated lithium silicate as highly efficient low-temperature sorbents for CO2 capture - Subha, P.; Nair, Balagopal; Visakh, V.; Sreerenjini, C.; Peer Mohamed, A.; Warrier, K.; Yamaguchi, T.; Hareesh, U. (R S C Publications, 2018)
© 2018 The Royal Society of Chemistry. Carbon dioxide emission from massive point sources such as industries and power plants is perceived to be a major contributor towards global warming and associated climate changes. Although lithium silicate has the highest capacity for CO2sorption (8 mmol g-1), it is kinetically limited during the sorption process, particularly at temperatures below 500 °C. Herein, we report a facile strategy for the development of germanium-incorporated lithium silicate composites, which display enhanced CO2absorption capacity as well as kinetics in the temperature range of 150-680 °C. The absorption capacity of 324 mg g-1at the rate of 117 mg g-1min-1was measured at 680 °C, and 49 mg g-1at the rate of 36 mg g-1min-1was measured at 300 °C for samples with a Si:Ge molar ratio of 1:0.183. This study thus highlights the possibility of employing germanium-incorporated lithium silicates for the absorption of CO2at a wide range of temperatures, including the in situ removal of CO2from chemical and petrochemical reactions, such as the water-gas shift reaction occurring at low temperature ranges of 150-450 °C, that has hitherto been not possible with pure Li4SiO4.